Effect of Working Capital Management and Earnings Management on Stock Return of Digital Bank Companies Listed on the Indonesia Stock Exchange - Ari Purwanti (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2022)
This study aims to determine the effect of working capital and earnings management on the stock returns of digital bank companies listed on the Indonesia Stock Exchange. This research uses quantitative research with a case study approach. The research variables are divided into the dependent variable (working capital management and company profit management) and the independent variable (stock returns). The working capital management variable uses the Cash Conversion Cycle (CCC) proxy, while the company's Earnings Management variable uses the Efficient Earning Management (EEM) proxy. Analysis of research data using the SPSS 19.0 for windows program and several analytical techniques, namely normality test, coefficient of determination (R2), F statistical test, and t statistical test. Based on the results and data analysis in this study, it can be concluded that digital bank stock returns are not influenced by the company's working capital management but are positively and significantly influenced by its earnings management.